The Role of Lactic Acid in the Management of Bacterial Vaginosis: A Systematic Literature Review - Werner Mendling; Maged Atef El Shazly; Lei Zhang (MDPI AG, 2022)
Bacterial vaginosis (BV) is a common infection characterized by an imbalance in the vaginal microbiome. Alongside the extensive research for effective therapies, treatment recommendations for symptomatic BV with antibiotics have been developed and are currently available. However, the recurrence of BV remains a considerable challenge given that about 60% of women experience BV relapse within six months after initial treatment. In addition, clear guidelines on the treatment of asymptomatic BV during pregnancy or for BV mixed infections are still missing. Lactic acid has been put forward as a potential treatment or for prophylaxis of BV due to its ability to restore the imbalance of the vaginal microbiota and to promote the disruption of vaginal pathogenic bacterial biofilms, which might trigger BV recurrence. This review evaluates the clinical evidence regarding the efficacy and prophylactic potential of lactic acid in BV through a systematic literature search. In addition, a treatment regimen consisting of lactic acid as a standalone treatment or in combination with current recommended therapies for practice is suggested based on these findings and stratified according to BV severity, pregnancy status, and coincidence with vulvovaginal candidosis (VVC) or trichomoniasis.